1996
DOI: 10.1002/jbmr.5650110307
|View full text |Cite
|
Sign up to set email alerts
|

Increased bone turnover in late postmenopausal women is a major determinant of osteoporosis

Abstract: Changes of bone turnover with aging are responsible for bone loss and play a major role in osteoporosis. Although an increase of bone turnover has been documented at the time of menopause, the subsequent abnormalities of bone resorption and formation and their potential role in determining bone mass in the elderly have not been investigated. To address this issue, we have measured a battery of new sensitive and specific markers of bone turnover in a population-based study of 653 healthy women analyzed cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
309
5
12

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 888 publications
(345 citation statements)
references
References 44 publications
19
309
5
12
Order By: Relevance
“…On another hand, in late postmenopausal women, resorption was more important than that observed in early postmenopausal women. These data are in accordance with these obtained by Garnero et al (1996) in elderly women, a high bone turnover rate was being associated with a low bone mass. Moreover, Cheong et al (2007) showed that soy protein containing up to 135.5 mg isofl avones/day for 50 days, did not suppress bone resorption in late postmenopausal women (Ͼ6 years since menopause).…”
Section: Discussionsupporting
confidence: 93%
“…On another hand, in late postmenopausal women, resorption was more important than that observed in early postmenopausal women. These data are in accordance with these obtained by Garnero et al (1996) in elderly women, a high bone turnover rate was being associated with a low bone mass. Moreover, Cheong et al (2007) showed that soy protein containing up to 135.5 mg isofl avones/day for 50 days, did not suppress bone resorption in late postmenopausal women (Ͼ6 years since menopause).…”
Section: Discussionsupporting
confidence: 93%
“…The OFELY cohort has been described elsewhere. (16,17) Briefly, OFELY is an ongoing prospective study of the determinants of bone loss in 1039 volunteer women, recruited between February 1992 and December 1993, 31 to 89 years of age, randomly selected from the affiliates of a large health insurance company (Mutuelle Gé né rale de l'Education Nationale) from the Rhô ne District (ie, Lyon and its surroundings in France), with an annual follow-up. Written informed consent was obtained from each woman, and the study was approved by the local ethics committee.…”
Section: Subjectsmentioning
confidence: 99%
“…Moreover, overall bone turnover is significantly increased in peri-and postmenopausal women but in an imbalanced fashion. Bone resorption increases, at 90%, and bone formation increases at only 45%, resulting in a net loss of bone mineral density (11). The exact mechanism through which bone formation after menopause cannot keep up with bone resorption remains unknown.…”
mentioning
confidence: 99%